THE USAGE OF CLOUD SERVICES IN THE PROCESS OF PROFESSIONAL TRAINING OF PROGRAMMERS AT HIGHER EDUCATIONAL INSTITUTIONS - Spirin O.; Eremeev V. (Kherson State University, 2017)
In the article the state of the art and the main tendencies of cloud computing development are analyzed. The importance of cloud technologies application in education is grounded. The directions of their appliance are examined in higher education, in particular as for the creation of the cloud-oriented learning scientific environment at educational institutions. The advantages of transfer of IT-infrastructure of higher educational institutions into the cloud form are shown (the economy of funds for purchase of software and renovation of computer database; the reduction of the need for specially equipped premises; the creation of an open educational environment). The main directions of the research study of cloud technologies application in the process of professional training of programmers are characterized, among them there are: 1) formation of skills of the cloud services use for the professional tasks solving; 2) formation of skills of the development of cloud applications, deployment of cloud infrastructure, cloud applications and data bases security support. The description of cloud services that can be used in the process of programming learning and usage of training projects (Ideone, Codenvy, DbDesigner) are provided. The brief description of the possibilities of the Amazon platform usage for formation of cloud software development skills is provided.